Activation of KIT modulates the function of tumor necrosis factor‐related apoptosis‐inducing ligand receptor (TRAIL‐R) in mast cells. Issue 7 (16th April 2015) - Förster, A.; Grotha, S. P.; Seeger, J. M.; Rabenhorst, A.; Gehring, M.; Raap, U.; Létard, S.; Dubreuil, P.; Kashkar, H.; Walczak, H.; Roers, A.; Hartmann, K.
Abstract Background Mastocytosis is characterized by the accumulation of mast cells (MCs) associated with activating mutations of KIT. Tumor necrosis factor‐related apoptosis‐inducing ligand receptors (TRAIL‐Rs) are preferentially expressed on neoplastic cells and induce the extrinsic apoptotic pathway. Recent studies reported on the expression of TRAIL‐Rs and TRAIL‐induced apoptosis in cultured human MCs, which depend on stem cell factor (SCF)‐induced or constitutive KIT activation. Material and methods We sought to further define the impact of TRAIL‐Rs on MCs in vivo and in vitro. Using Cre/loxP recombination, we generated mice with MC‐specific and ubiquitous knockout of TRAIL‐R. In these mice, anaphylaxis and numbers of MCs were investigated. We also explored the expression and function of TRAIL‐Rs in cultured murine and human MCs upon activation of KIT. By conducting immunofluorescence staining, we analyzed the expression of TRAIL‐Rs in MCs infiltrating the bone marrow of patients with mastocytosis. Results MC‐specific deletion of TRAIL‐R was associated with a slight, but significant increase in anaphylaxis. Numbers of MCs in MC‐specific knockouts of TRAIL‐R were comparable to controls. Whereas cultured IL‐3‐dependent murine MCs from wild‐type mice were resistant to TRAIL‐induced apoptosis, SCF‐stimulated MCs underwent apoptosis in response to TRAIL. Interestingly, activating KIT mutations also promoted sensitivity to TRAIL‐mediated apoptosis in human MCs. In line with these findings, MCs infiltrating the bone marrow of patients with mastocytosis expressed TRAIL‐R1. Conclusions Activation of KIT regulates the function of TRAIL‐Rs in MCs. TRAIL‐R1 may represent an attractive diagnostic and therapeutic target in diseases associated with KIT mutations, such as mastocytosis.